Strategi Guru PPKn dalam Pembentukan Moral pada siswa di SMA Negeri 2 Kolaka - Asis, Rahmi Ramadhani Abdul; Sopiandy, Dede; Hariyadi, Slamet (Universitas Hamzanwadi, 2026)
The decline in students moral quality, reflected in low discipline, responsibility, and social awareness, has become a serious challenge in education amid globalization and rapid digital development. This condition highlights the strategic role of teachers, particularly civics education (ppkn) teachers, in fostering students’ moral development in a contextual and sustainable manner. This study aims to analyze in depth the strategies employed by ppkn teachers in shaping students’ morality at SMA Negeri 2 Kolaka, as well as examining the support, constraints, and efforts of the school environment in this process. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving ppkn teachers, the principal, the vice principal for student affairs, and students. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The findings reveal that the strategies used by ppkn teachers in moral formation are holistic, integrative, and contextual. Teachers implement contextual moral discussion-based learning combined with exemplary behavior in daily school life. This strategy encourages moral internalization through reflection, moral decision-making, and the habituation of positive behavior. Furthermore, the integration of local socio-cultural values and social interaction among students strengthens the moral formation process. The school environment supports moral development through value-based school culture, habituation programs, and a humanistic guidance system. Despite internal and external challenges, adaptive strategies implemented by teachers and the school contribute to positive changes in students’ moral behavior. This study emphasizes that effective moral education requires synergy between pedagogical strategies, teacher exemplarity, and institutional school support.